Penggunaan Nomina Kyoku dan Uta pada Kolom Komentar Youtube - Yeni Yeni; Gede Satya Hermawan (Undiksha Press, 2021)
This paper describes the use of words that are synonymous or have the same meaning. The words chosen are Kyoku and Uta, each of which refers to the meaning of the song. For Japanese language learners, the word Uta is better known to refer to the meaning of a song, and Ongaku refers to the meaning of music. This study will show that in its use the word Uta can be replaced with the word Kyoku, which generally refers to the meaning of the song. But Kyoku shows a more specific meaning. The data is taken from the YouTube comments on popular Japanese songs. Three songs were selected that are in the top three of the Oricon Chart, namely: Gomen ne Finger Crossed (Nogizaka 46); Hitori ni Shinai yo (Kanjani 8), and Pale Blue (Kenshi Yonezu).